Noradrenergic Regulation of Hippocampus-Dependent Memory - Nguyen, Peter V.; Connor, Steven A. (Central Nervous System Agents in Medicinal Chemistry, 2019)
Neuromodulation regulates critical functions of CNS synapses, ranging from neural circuit development to high-order cognitive processes, including learning and memory. This broad scope of action is generally mediated through alterations of the strength of synaptic transmission (i.e. synaptic plasticity). Changes in synaptic strength are widely considered to be a cellular representation of learned information. Noradrenaline is a neuromodulator that is secreted throughout the brain in response to novelty or increased arousal. Once released, noradrenaline activates metabotropic receptors, initiating intracellular signaling cascades that promote enduring changes in synaptic strength and facilitate memory storage. Here, we provide an overview of noradrenergic modulation of synaptic plasticity and memory formation within mammalian neural circuits, which has broad applicability within the neurotherapeutics community. Advances in our understanding of noradrenaline in the context of these processes may provide a foundation for refining treatment strategies for multiple brain diseases, ranging from post-traumatic stress disorder to Alzheimer’s Disease.
Keywords: hippocampus